(untitled) (Research, Society and Development, 2021)
New ingredients have been used in extruded products to increase the healthiness and regionalization of these products. However, the process variables that can interfere with the technological quality of the product should be studied, aimed at good acceptance by consumers. This study aimed to evaluate the effects of the concentration of micronized roasted coffee (MRC) and the barrel temperature on the technological properties of rice-based extrudates. The extrudates were made with 3 and 8% MRC to replace rice flour and processed in a mono-extruder at 140 and 180 oC. They were characterized for color, expansion index, hardness, bowl-life, porosity, water absorption index, and solubility index, and paste properties. To assess the effects of the process variables, analysis of variance, and Scott-Knott test (p <0.05) were applied to compare the means. The increase in MRC concentration reduced the color parameters and hardness, while the increase in temperature affected the expansion index. A joint effect of the variables concentration and temperature was observed for the other properties evaluated. The study showed that MRC is a potential source of fibers and natural pigments, with a direct effect on the main technological properties of the final product.